Selective vulnerability of αOFF retinal ganglion cells during onset of autoimmune optic neuritis - Mayer, Christina; Bruehl, Claus; Salt, Emma L.; Diem, Ricarda; Draguhn, Andreas; Fairless, Richard (Neuroscience, 2018)
Retinal ganglion cells (RGCs), a diverse body of neurons which relay visual signals from the retina to the higher processing regions of the brain, are susceptible to neurodegenerative processes in several diseases affecting the retina. Previous evidence shows that RGCs are damaged at early stages of autoimmune optic neuritis (AON), prior to subsequent degeneration of the optic nerve. In order to study cell type-specific vulnerability of RGCs we performed immunohistochemical and patch-clamp electrophysiological analyses of RGCs following induction of AON using the experimental autoimmune encephalomyelitis model in Brown Norway rats. We report that αRGCs are more susceptible to degeneration than the global RGC population as a whole, with functional and structural changes beginning even prior to demyelination and inflammatory infiltration of the optic nerve (where the RGC axons reside). Functional classification of αRGCs into OFF-sustained, OFF-transient and ON-sustained subtypes revealed that αOFF RGCs (both sustained and transient subtypes) are more vulnerable than αON RGCs, as indicated by reductions in light-evoked post-synaptic currents and retraction of dendritic arbours. Classification of neuronal susceptibility is a first step in furthering our understanding of what underlies a neuron's vulnerability to degenerative processes, necessary for the future development of effective neuroprotective strategies.